2021
DOI: 10.1002/advs.202002874
|View full text |Cite
|
Sign up to set email alerts
|

OTUD1 Activates Caspase‐Independent and Caspase‐Dependent Apoptosis by Promoting AIF Nuclear Translocation and MCL1 Degradation

Abstract: Apoptosis‐inducing factor (AIF) plays a dual role in regulating cell survival and apoptosis, acting as a prosurvival factor in mitochondria via its NADH oxidoreductase activity and activating the caspase‐independent apoptotic pathway (i.e., parthanatos) after nuclear translocation. However, whether one factor conjunctively controls the separated functions of AIF is not clear. Here, it is shown that OTU deubiquitinase 1 (OTUD1) acts as a link between the two functions of AIF via deubiquitination events. Deubiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 57 publications
0
36
0
Order By: Relevance
“…OTUD1 induced apoptotic cancer cell death through p53 stabilization 10 . Recently, Luo et al reported that OTUD1 induced stabilization of DCAF10 and recruited the cullin 4A damage‐specific DNA binding protein 1 (DDB1) to promote Mcl‐1 ubiquitination 33 …”
Section: Discussionmentioning
confidence: 99%
“…OTUD1 induced apoptotic cancer cell death through p53 stabilization 10 . Recently, Luo et al reported that OTUD1 induced stabilization of DCAF10 and recruited the cullin 4A damage‐specific DNA binding protein 1 (DDB1) to promote Mcl‐1 ubiquitination 33 …”
Section: Discussionmentioning
confidence: 99%
“…Whereas, in Otud1 -/--MEFs, increased intranuclear AIFM1 was detected concomitantly with the reduced mitochondrial AIFM1 (Extended Data Fig. 5c), which may affect mitochondrial oxidative phosphorylation and ROS generation 20 . These results indicated that OTUD1 physiologically binds and regulates the K63-ubiquitylation of KEAP1 under basal conditions and is important for the efficient antioxidative stress response, ROS production, and oxeiptosis.…”
Section: Otud1 Regulates Keap1-mediated Oxidative Stress Response and Cell Deathmentioning
confidence: 92%
“…In this study, we examined the effects of 88 human DUBs on LUBAC-mediated NF-κB activation, and identified an OTU-family DUB, OTUD1 (also known as DUBA7) 17 , as the most potent down-regulator. OTUD1 reportedly regulates tumour progression 18 , cell death 19,20 , innate immune responses [21][22][23] , YAP signalling 24 , autoimmune disease 25 , iron transport 26 , and inhibition of colonic inflammation 27 , whereas the regulatory mechanism of OTUD1 on the NF-κB pathway has not been revealed.…”
mentioning
confidence: 99%
“…However, xanthohumol downregulated HK2 and glycolysis and subsequently increased cytochrome c release to activate the intrinsic (mitochondrial) apoptotic pathway in the HT29, SW480, LOVO, HCT116, and SW620 colorectal cancer cell lines [13]. The apoptosis-inducing factor (AIF), a mitochondrial protein, is implicated in caspase-independent programmed cell death following its translocation to the nucleus [110]. In an in vitro investigation using multiple biochemical assays, xanthohumol was detected to cause proliferation inhibition and death of the rat glioma C6 cells (in a time-and dose-dependent manner) via a mechanism of inducing AIF pathway apoptosis by triggering mitochondrial stress [111].…”
Section: Cancermentioning
confidence: 99%